Neonatal patient triggered ventilation. Issue 4 (April 1988) - Greenough, A; Pool, J
Abstract : Patient triggered ventilation was assessed in 14 neonates (gestational age 24-40 weeks). Inspiratory changes in airflow, monitored by a pneumotachograph, were used to trigger the ventilator and this was not associated with complications. Patient triggered ventilation was maintained for up to eight hours (mean duration five hours). In 13 of 14 infants oxygenation improved and this was associated in most with an increase in rate of delivered positive pressure inflations and inflating volumes. A greater improvement in oxygenation was shown when trigger mode was used during the recovery phase of respiratory distress syndrome. Only one infant, who made very little respiratory effort, failed to improve. We conclude that patient triggered ventilation may be used as an effective form of neonatal ventilation.